Reorientação curricular na RME-SP: a utilização dos cadernos de apoio e aprendizagem por alunos e professores do ciclo I - análise da integração entre mídia e currículo - Neves, Daniela da Costa (2011)
This research started from seeking the need for actions by the Secretaria Municipal de Educação de São Paulo that would give subsidies to teaching materials and also to the process of training of teachers of elementary school with different skills (Ensino Fundamental I), in view of needing for materials that were aligned with the curriculum reorientation implemented in 2008 and the difficulties presented by students in results of external evaluations conducted from 2007. The plot of this research were the Cadernos de apoio e aprendizagem, produced by the Secretaria Municipal de Educação in partnership with Padre Anchieta Foundation, whose use by teachers and students from public schools began in 2010. This material consists of teacher`s and students books and videos that integrate the activities proposed in the printed material. Our goal was to demonstrate if the Cadernos de apoio e aprendizagem subsidized the educational practices and how they did it, highlighting the contributions and challenges perceived by elementary school students and teachers in their work integrating media and curriculum. Twenty eight teachers and a hundred students from five schools belonging to the Departaments of educational of Butantã, Campo Limpo and Penha from elementary school were interviewed. The techniques for data collection were questionnaires with structured and semi-structured questions and class observations. For the data analysis the option was for the qualitative approach, extracting the central idea of the issues and the cluster of categories by convergences. Analysis and interpretation of data demonstrated that the use of Cadernos de apoio e aprendizagem facilitated the preparation of the syllabus by the teacher, aroused to the interest of the student to learn both graphical format for printed material and by integration with the videos, made the teaching / learning process more meaningful by addressing issues related to the daily lives of students and to São Paulo city and favored a more effective dynamic range and methodological strategies. Among the challenges faced by teachers are the adequacy of school time, overcoming the setbacks caused by delays in delivery of materials, the video display, for lack of sufficient equipment in some schools and carry out the suitability of the material to students with difficulties and learning disabilities. In the end the conclusion was that the Cadernos de apoio e aprendizagem subsidized educational practices, providing an integrated curriculum among the public schools and with the use of media in education